Training extension workers in population/rural development relations at farm and family level : Philippine experience - 230935 Sison, Obdulia F.; Association of Asian Agrifcultural Colleges and Universites (AAACU) Biennial Convention (3rd : 1978 : Unversiti Pertanian Malaysia) (Obdulia F Sison : Serdang Universiti Pertanian Malaysia, 1978)
28